Sustainable high-strength alkali-activated slag concrete is achieved by recycling emulsified waste cooking oil - Huang, Jinguang; Huo, Yanlin; Su, Qunshan; Lu, Dong; Wu, Yuanchao; Dong, Xinhong; Gao, Yang (Frontiers in Materials, 2024)
To mitigate the shrinkage of high-strength alkali-activated slag concrete (AASC), this paper introduces emulsified cooking oil (ECO) and emulsified waste cooking oil (EWCO) into the AASC system. The effects of admixing ECO and EWCO on the compressive strength, drying shrinkage, autogenous shrinkage, carbonation, and sulfuric acid resistance of the AASC are systematically explored. The optimization mechanism is also proposed based on the surface tension and microstructural analysis. The experimental results show that the admixing ECO and EWCO slightly reduce the compressive strength of the AASC by 7.8%. Interestingly, the admixing ECO and EWCO significantly reduce the drying shrinkage and autogenous shrinkage, simultaneously improving the resistance to carbonation and sulfuric acid of the AASC. Specifically, the introduction of 2 wt.% ECO and EWCO can reduce the autogenous shrinkage of the AASC by 66.7% and 41.0%, respectively. Microstructural observations reveal that the addition of ECO and EWCO can reduce ` the internal surface tension of the AASC, improve the transport and diffusion of the pore solution, and increase the absorbable free water of the slag, which in turn reduces the shrinkage of the composites. It also increases the ionic concentration in the pore solution, resulting in a more complete reaction of the AASC, which can optimize the pore structure and thus improve the durability of the AASC. This study proposes a promising way to develop sustainable alkali-activated slag concrete achieved by recycling waste materials.